The portrayal of migrants and liminality in Nadifa Mohamed's Black Mamba Boy, The Orchard of Lost Souls and The Fortune Men - Fühner, Melissa Ashleigh (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
This thesis argues that the characters in Nadifa Mohamed's oeuvre exhibit both vulnerability and agency and that their position in society oscillates as if between two poles, as they cross social and spatial boundaries. There is no existing scholarly research that focuses on child migrants in Mohamed's texts specifically. Here, Black Mamba Boy, The Orchard of Lost Souls and The Fortune Men are analysed and compared with a central focus on the child migrant characters to examine her portrayal of conflict-induced migration and its impact on vulnerable communities. In Black Mamba Boy, Mohamed portrays Jama's exilic journey where he leaves his homeland of Hargeisa and migrates across territorial borders in Northeast Africa to find his father. His quest brings him from Somaliland to Sudan as he walks through countries that are devastated by the war between the British and Italian colonial forces in the 1930s. As Jama attempts to cross the spatial distance between himself and his father he also treads the invisible line between life and death. Along his journey, Jama is exploited and abused by colonial troops and traumatised by the conflict he witnesses. Mohamed revisits her father's precarious journey not to portray him as a victim but to make him "a hero, not the fighting or romantic kind but the real deal, the starved child who survives every sling and arrow that shameless fortune throws at them" (1). Thus, the text is an account of Jama's strength as he miraculously survives the brutalities of war. Similarly, in The Orchard of Lost Souls, the child protagonist, Deqo, is a refugee with parents. She internally migrates through Hargeisa at the moment the region breaks out into the Somali Civil War. Deqo attempts to keep herself out of harm's way as the town is destroyed by soldiers and rebel groups who have opened fire against civilians. As a female child migrant Deqo occupies a particularly vulnerable position as she navigates a space where gender-based violence is used as a method of war. Despite the dangers around her, Deqo actively seeks out safety and a path that will free her from the tightening grip of the war. The Fortune Men depicts Mahmood's journey of migration as an adult. When he attempts to cross the border into Wales he is ostracised, abused, and dehumanised because of his difference. Jama and Deqo's exilic journeys are compared to Mahmood's unsuccessful migration and the children cross borders that adults cannot cross because they use their vulnerability to seek out opportunities and change their environment. This thesis is situated within the theoretical framework of transnational and diasporic literature with a specific focus on the impact of forced migration on child migrants. Through close engagement and comparison of the three primary ii texts mentioned, this thesis demonstrates the vulnerabilities and fluctuating agencies of characters to highlight their liminal positioning.
Keywords: Mohamed, Nadifa, 1981- -- Criticism and interpretation; Diaspora; Transnationalism in literature; Migration studies; Liminality in literature; African literature (English) -- History and criticism